Soliton molecules, Y-type soliton and complex multiple soliton solutions to the extended (3+1)-dimensional Jimbo-Miwa equation - Wang, Kang-Jia (Physica scripta, 2024)
The central purpose of this paper is extracting some novel and interesting soliton solutions of the extended (3+1)-dimensional Jimbo-Miwa equation(JME) which acts as an extension of the classic (3+1)-dimensional JME for the plasma and optics. First, we study the N -soltion solutions that is developed by the Hirota bilinear method (HBM). Then, the soliton molecules and Y -type soliton solutions are constructed via imposing the novel resonance conditions to the N -soltion solutions. In addition, we also explore the complex multiple soliton solutions via the HBM. The dynamic properties of the N -soltion, soliton molecules, Y -type soliton as well as the complex multiple soliton solutions are presented graphically. The developed soliton solutions of this research are all new and can enable us apprehend the nonlinear dynamic behaviors of the extended (3+1)-dimensional JME better.